Encyclopedia of Water 2019
DOI: 10.1002/9781119300762.wsts0161
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication and Nutrient Fluxes in Mediterranean Coastal Lagoons

Abstract: In this article, we provide a general overview of eutrophication in aquatic ecosystems, with a focus on the Mediterranean Sea and two Sardinian lagoons (western Mediterranean Sea, Italy), as case studies. In the Cabras Lagoon, we assessed the nutrient budget and fluxes using the biogeochemical Land–Ocean Interaction Coastal Zone model. High nutrient and chlorophyll‐ a concentrations indicated eutrophic conditions, summer being the most critical season as related to the decrease in river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 78 publications
0
9
0
2
Order By: Relevance
“…According to Nixon (1982Nixon ( , 1995, the combination of low flushing rates and terrestrial nutrient inputs make coastal lagoons high primary production zones, which can lead to phytoplankton blooms, oxygen depletion and eutrophication. The depletion of oxygen due to the decomposition of lagooninhabiting vegetation has previously been reported in Venice, Italy (Tagliapietra et al, 2011) and eutrophication-impacted lagoons have also been reported in the USA (Glibert et al, 2014) and along the Mediterranean coast (Padedda et al, 2019). While some lagoons can potentially selfregulate the effects of eutrophication through top-down control over phytoplankton (Pérez-Ruzafa et al, 2002, the impacts of excess nutrients on lagoon-inhabiting species is not well understood, especially in Small Island Developing States (SIDS) where urban development and intensive agriculture are mostly concentrated along the coast.…”
Section: Ocean Warming and Eutrophication: Major Threats To Coastal Lagoonsmentioning
confidence: 69%
“…According to Nixon (1982Nixon ( , 1995, the combination of low flushing rates and terrestrial nutrient inputs make coastal lagoons high primary production zones, which can lead to phytoplankton blooms, oxygen depletion and eutrophication. The depletion of oxygen due to the decomposition of lagooninhabiting vegetation has previously been reported in Venice, Italy (Tagliapietra et al, 2011) and eutrophication-impacted lagoons have also been reported in the USA (Glibert et al, 2014) and along the Mediterranean coast (Padedda et al, 2019). While some lagoons can potentially selfregulate the effects of eutrophication through top-down control over phytoplankton (Pérez-Ruzafa et al, 2002, the impacts of excess nutrients on lagoon-inhabiting species is not well understood, especially in Small Island Developing States (SIDS) where urban development and intensive agriculture are mostly concentrated along the coast.…”
Section: Ocean Warming and Eutrophication: Major Threats To Coastal Lagoonsmentioning
confidence: 69%
“…Transitional water environments represent the natural, physical, and functional transition between terrestrial ecosystems and the sea [1][2][3]. These peculiar areas are often very productive and unique ecosystems around which many human commercial activities revolve [2,4,5]. Ecosystem services integrate ecology and economics issues to better understand the effects of human policies and impacts on both ecosystem function and human wellbeing [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…NPOC (not purgeable organic carbon) refers to the nonvolatile fraction of organic carbon [24]. All these carbon fractions play a vital role as a vector of matter and energy in the lagoon ecosystems, both for the organic compart and the sedimentological one [2,4,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to support the implementation of European Union marine policies such as the Marine Strategy Framework Directive (MSFD) and the Common Fisheries Policy (CFP) the European FP7 project COMMON SENSE aimed to develop cost-effective, easy to use, sensitive sensors for environmental monitoring (Ribotti et al, 2015). One of the core research goals was to develop costeffective sensors to increase the availability of standardised data on eutrophication (Padedda et al, 2019) in European marine regions and sub-regions.…”
Section: Introductionmentioning
confidence: 99%